Efficacy Of Macmiror® In The Therapy Of Giardiasis Invasion In Children With Chronic Hapatitis B - Nurmatova Nargiza Fatkhullayevna, Inoyatova Flora Ilyasovna, Asilbekova Malokhat Azadovna, Mirsalikhova Nargis Khayrullayevna (International Journal of Advanced Science and Technology, 2020)
Application of three-stage therapy of giardiasis in 250 children with CHB, using MACMIROR®, Albendazole, and Metronidazole at the second stage of effecting the parasite and its elimination from the organism, provided achievement of clinical-biochemical remission in 91.1%, 72.5% and 52,5% cases, and parasite elimination in 93.3%, 32.5% and 60.0% cases, respectively. It should be noted, that in the conditions of administration of Trichopolum, in spite of the high rate of  G.Lamblia elimination, the therapy was associated with the expressed hepatic toxicity, making recommendation of it for that category of children impossible. Thus, the first line agent for a specific therapy of giardiasis in children with CHB is MACMIROR®, due to its efficacy and safety.